Chemotherapy-Induced Peripheral Neurotoxicity as A Risk Factor for Poor Sleep Quality in Breast Cancer Survivors Treated with Docetaxel - Ya-Ning Chan; You-Wun Jheng; Ya-Jung Wang (Elsevier, 2021)
Objective: The purpose of this study was to explore sleep quality and to determine whether chemotherapy-induced peripheral neurotoxicity is a risk factor for poor sleep quality in breast cancer survivors who receive docetaxel treatment. Methods: Secondary data analysis from a cross-sectional study. Sample characteristics were collected using an information sheet. Independent variables included the Hospital Anxiety and Depression Scale (HADS), the Patient Neurotoxicity Questionnaire (PNQ), and the Identification Pain Questionnaire (ID pain). Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). We performed descriptive analyses and simple logistic regression. Results: A total of 98 participants were included. More than 60% of them reported poor sleep quality, with their average PSQI score being 7.54 ± 4.45. Poor subjective sleep quality (1.37 ± 0.88) and short sleep duration (1.37 ± 1.08) were their main problems. In addition, significant risk factors for poor sleep quality were chronic illness (odds ratio [OR] = 2.753, P = 0.041), anxiety (OR = 7.714, P = 0.009), neuropathic pain (OR = 11.261, P = 0.022), sensory neuropathy (OR = 2.529, P = 0.032), motor neuropathy (OR = 3.781, P = 0.002), and undergoing chemotherapy (OR = 2.593, P = 0.027). Targeted therapy that some survivors received served as a protective factor (OR = 0.351, P = 0.015). Conclusions: We found a high prevalence of poor sleep quality in breast cancer survivors treated with docetaxel. The results indicated that, in addition to clinical characteristics and psychological discomfort, chemotherapy-induced peripheral neurotoxicity is a significant risk factor for poor sleep quality.